Functional Role of Class III Myosins in Hair Cells - Cirilo, Joseph A.; Gunther, Laura K.; Yengo, Christopher M. (Frontiers in Cell and Developmental Biology, 2021)
Cytoskeletal motors produce force and motion using the energy from ATP hydrolysis and function in a variety of mechanical roles in cells including muscle contraction, cargo transport, and cell division. Actin-based myosin motors have been shown to play crucial roles in the development and function of the stereocilia of auditory and vestibular inner ear hair cells. Hair cells can contain hundreds of stereocilia, which rely on multiple myosin isoforms to elongate, organize, and stabilize their structure. Mutations in many stereocilia-associated myosins have been shown to cause hearing loss in both humans and animal models suggesting that each myosin isoform has a specific function in these unique parallel actin bundle-based protrusions. Here we review what is known about myosins that function in the stereocilia, with a special focus on class III myosins that harbor point mutations associated with delayed onset hearing loss. Much has been learned about the role of the two class III myosin isoforms, MYO3A and MYO3B, in maintaining the precise stereocilia lengths required for normal hearing. We propose a model for how class III myosins play a key role in regulating stereocilia lengths and demonstrate how their motor and regulatory properties are particularly well suited for this function. We conclude that ongoing studies on class III myosins and other stereocilia-associated myosins are extremely important and may lead to novel therapeutic strategies for the treatment of hearing loss due to stereocilia degeneration.